Seed Quality as Influenced by Film Coating WithMicronutrients, Fungicide and MicrobialConsortium in Chickpea - BASAMMA KORI; ASHOK S. SAJJAN (Seed Research, 2026)
The laboratory experiment was carried out in Department of Seed Science and Technology, College of Agriculture, Vijayapura during rabi 2020-2021. Chickpea seeds of BGD-111-1 variety were coated with polymer, micronutrient, fungicide and microbial consortium used for sowing. The harvested seed was cleaned and used for seed quality parameter studies. Among the eight different treatments, film coat (Genius coat) @ 6 ml + ZnSO4 @ 2 g + FeSO4 @ 2 g + Boron @ 2 g + Ammonium molybdate @ 2 g + microbial consortium @ 8 ml + Carbendazim@ 3.5 g /kg of seed recorded significantly higher seed quality parameters like higher seed germination percentage (94.96%), shoot length (8.26 cm), root length (18.94 cm), seedling vigour index I (2632), seedling vigour index II (27365) and biochemical parameters like protein (22.48%), dehydrogenase activity (0.782 OD value) and lower electrical conductivity (0.705 dS/m).